2000
DOI: 10.1128/iai.68.8.4531-4538.2000
|View full text |Cite|
|
Sign up to set email alerts
|

Differential Modulation and Subsequent Blockade of Mitogenic Signaling and Cell Cycle Progression byPasteurella multocidaToxin

Abstract: The intracellularly acting protein toxin of Pasteurella multocida (PMT) causes numerous effects in cells, including activation of inositol 1,4,5-trisphosphate (IP 3 ) signaling, Ca 2؉ mobilization, protein phosphorylation, morphological changes, and DNA synthesis. The direct intracellular target of PMT responsible for activation of the IP 3 pathway is the G q/11 ␣-protein, which stimulates phospholipase C (PLC) ␤1. The relationship between PMT-mediated activation of the G q/11 -PLC-IP 3 pathway and its ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
48
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
4
1

Relationship

5
5

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 45 publications
6
48
0
Order By: Relevance
“…For subconfluent HEp-2 cell monolayers, 8-well chamber slides (Lab-Tek) were seeded with 6 ϫ 10 4 cells/well in complete EMEM and incubated for no more than 24 h (ϳ80% confluent) before use. Confluent HEp-2 cell monolayers were prepared according to a method previously described for Vero cells (40). HEp-2 cells were seeded into 8-well chamber slides at a density of 3 ϫ 10 4 cells/well and incubated for 72 h. The medium in each well was then removed and replaced with complete EMEM that contained 1% fetal calf serum.…”
Section: Methodsmentioning
confidence: 99%
“…For subconfluent HEp-2 cell monolayers, 8-well chamber slides (Lab-Tek) were seeded with 6 ϫ 10 4 cells/well in complete EMEM and incubated for no more than 24 h (ϳ80% confluent) before use. Confluent HEp-2 cell monolayers were prepared according to a method previously described for Vero cells (40). HEp-2 cells were seeded into 8-well chamber slides at a density of 3 ϫ 10 4 cells/well and incubated for 72 h. The medium in each well was then removed and replaced with complete EMEM that contained 1% fetal calf serum.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have revealed that in addition to the ␣ subunit of the heterotrimeric G q protein (488)(489)(490), PMT also acts on other G proteins, i.e., G 11 , G i , and G 12/13 (488)(489)(490)(491)(492)(493)(494). A number of studies have implicated PMT as a modulator of host immunity (475,(495)(496)(497)(498) and cellular differentiation and proliferation (476,477,485,(499)(500)(501)(502)(503)(504)(505)(506)(507). Interestingly, because of its potent mitogenic and proliferative properties, there has been speculation that exposure to PMT might play a role in cancer predisposition as a longterm consequence of infection with toxinogenic P. multocida (485,495,499,504,505,(508)(509)(510).…”
Section: Survival In the Host Environmentmentioning
confidence: 99%
“…First, PMT-induced stimulation of PLC␤ signaling pathways were described (9), which were then shown to be caused by activation of G␣ q (10). G␣ q activation leads to mitogenic signaling through mitogen-activated protein kinase phosphorylation (11)(12)(13) and to stimulation of signal transducer and activator of transcription 1, 3, and 5 through Janus kinase phosphorylation (14). Gene knock-out and reconstitution experiments using G␣ q/11 -deficient mouse embryonic fibroblasts (MEFs) indicated that only G␣ q , and not the closely related G␣ 11 , is activated by PMT (15,16).…”
mentioning
confidence: 99%